An efficient in vitro propagation protocol for Pinguicula lusitanica, a rare insectivorous plant - Gonçalves, Sandra (2013)
In this study, an efficient protocol was developed for in vitro propagation of Pinguicula lusitanica L., a rare insectivorous plant with pharmacological value and limited reproductive capacity. The effects of two concentrations (0.1 and 0.5 mg l-1) of a range of plant growth regulators, including cytokinins (BA, KIN, and ZEA) and auxins (IAA, IBA, and NAA), and three concentrations of MS medium macronutrients (total, 1/2 and 1/4MS) on proliferation and rooting, were investigated. P. lusitanica shoots showed abundant proliferation and rooting capacity, both of which were significantly influenced by MS medium strength. The use of 1/2MS supplemented with 0.5 mg l-1 BA or KIN ensure a 29-fold rate of proliferation. Best rooting frequency and higher root number and length were attained in 1/4MS medium containing 0.2 mg l-1 IAA. Sixty percent of the plantlets were successfully acclimatized to ex vitro conditions, exhibiting normal development. These plantlets can be used to replenish declining populations in the wild and/or for the extraction of bioactive compounds, reducing pressure on wild stocks.